Inflammatory cytokines promote the retrodifferentiation of tumor‐derived hepatocyte‐like cells to progenitor cells. Issue 6 (29th October 2014) - Dubois‐Pot‐Schneider, Hélène; Fekir, Karim; Coulouarn, Cédric; Glaise, Denise; Aninat, Caroline; Jarnouen, Kathleen; Le Guével, Rémy; Kubo, Takashi; Ishida, Seiichi; Morel, Fabrice; Corlu, Anne
<x xml:space="preserve">Abstract</x> Human hepatocellular carcinoma (HCC) heterogeneity promotes recurrence and resistance to therapies. Recent studies have reported that HCC may be derived not only from adult hepatocytes and hepatoblasts but also hepatic stem/progenitors. In this context, HepaRG cells may represent a suitable cellular model to study stem/progenitor cancer cells and the retrodifferentiation of tumor‐derived hepatocyte‐like cells. Indeed, they differentiate into hepatocyte‐ and biliary‐like cells. Moreover, tumor‐derived HepaRG hepatocyte‐like cells (HepaRG‐tdHep) differentiate into both hepatocyte‐ and biliary‐like cells through a hepatic progenitor. In this study we report the mechanisms and molecular effectors involved in the retrodifferentiation of HepaRG‐tdHep into bipotent progenitors. Gene expression profiling was used to identify genomic changes during the retrodifferentiation of HepaRG‐tdHep into progenitors. We demonstrated that gene expression signatures related to a poor‐prognosis HCC subclass, proliferative progenitors, or embryonic stem cells were significantly enriched in HepaRG progenitors derived from HepaRG‐tdHep. HepaRG‐tdHep retrodifferentiation is mediated by crosstalk between transforming growth factor beta 1 (TGFβ1) and inflammatory cytokine pathways (e.g., tumor necrosis factor alpha [TNFα] and interleukin 6 [IL6]). Signatures related to TNFα, IL6, and TGFβ activation pathways are induced within the first hour of retrodifferentiation. Moreover, specific activation or inhibition of these signaling pathways allowed us to determine that TNFα and IL6 contribute to the loss of hepatic‐specific marker expression and that TGFβ1 induces an epithelial‐to‐mesenchymal transition of HepaRG‐tdHep. Interestingly, the retrodifferentiation process is blocked by the histone deacetylase inhibitor trichostatin A, opening new therapeutic opportunities. Conclusion: Cancer progenitor cells (or metastasis progenitors) may derive from tumor‐derived hepatocyte‐like cells in an inflammatory environment that is frequently associated with HCC. (Hepatology 2014;60:2076–2089)